NPM in Indonesia: Budget Restructuring, Privatisation and Civil Service Reform - Arif Budy Pratama (JPAS (Journal of Public Administration Studies), 2019)
This paper aims to evaluate the application of New Public Management (NPM) in Indonesia’s public sector through a brief description of public sector reform implementation and its impact to achieve better management practices and quality of public service delivery. The global advice of NPM-based reform suggests that public sector reform should be focused on management of public spending, management of public enterprises, and civil service reform. Based on this premise, the main analysis on Indonesia’s NPM included national budget restructuring, privatisation on parastatals, and bureaucratic reform. Indonesia’s budget restructuring obtained more adequate progress than both privatisation and civil service reform because of its high degree in managerial autonomy and relatively free political environment. Further research is needed to validate this proposition and to explain why NPM succeed in some areas and fail in others.